Synaptogenic gene therapy with FGF22 improves circuit plasticity and functional recovery following spinal cord injury - Almir Aljović; Anne Jacobi; Maite Marcantoni; Fritz Kagerer; Kristina Loy; Arek Kendirli; Jonas Bräutigam; Luca Fabbio; Valérie Van Steenbergen; Katarzyna Pleśniar; Martin Kerschensteiner; Florence M Bareyre (EMBO Molecular Medicine)
Abstract Functional recovery following incomplete spinal cord injury (SCI) depends on the rewiring of motor circuits during which supraspinal connections form new contacts onto spinal relay neurons. We have recently identified a critical role of the presynaptic organizer FGF22 for the formation of new synapses in the remodeling spinal cord. Here, we now explore whether and how targeted overexpression of FGF22 can be used to mitigate the severe functional consequences of SCI. By targeting FGF22 expression to either long propriospinal neurons, excitatory interneurons, or a broader population of interneurons, we establish that FGF22 can enhance neuronal rewiring both in a circuit‐specific and comprehensive way. We can further demonstrate that the latter approach can restore functional recovery when applied either on the day of the lesion or within 24 h. Our study thus establishes viral gene transfer of FGF22 as a new synaptogenic treatment for SCI and defines a critical therapeutic window for its application.